Semiconducting electrodes for neural interfacing: a review. (3rd February 2023) - Ahnood, Arman; Chambers, Andre; Gelmi, Amy; Yong, Ken-Tye; Kavehei, Omid
Abstract : Neural recording, stimulation, and biochemical sensing using semiconducting electrodes in both electrical and optical domains are discussed. Their differences from metallic electrodes from the application and characterization perspective are highlighted. Abstract : In the past 50 years, the advent of electronic technology to directly interface with neural tissue has transformed the fields of medicine and biology. Devices that restore or even replace impaired bodily functions, such as deep brain stimulators and cochlear implants, have ushered in a new treatment era for previously intractable conditions. Meanwhile, electrodes for recording and stimulating neural activity have allowed researchers to unravel the vast complexities of the human nervous system. Recent advances in semiconducting materials have allowed effective interfaces between electrodes and neuronal tissue through novel devices and structures. Often these are unattainable using conventional metallic electrodes. These have translated into advances in research and treatment. The development of semiconducting materials opens new avenues in neural interfacing. This review considers this emerging class of electrodes and how it can facilitate electrical, optical, and chemical sensing and modulation with high spatial and temporal precision. Semiconducting electrodes have advanced electrically based neural interfacing technologies owing to their unique electrochemical and photo-electrochemical attributes. Key operation modalities, namely sensing and stimulation in electrical, biochemical, and optical domains, are discussed, highlighting their contrast to metallic electrodes from the application and characterization perspective.